The Remix: The Influence of Hip Hop Culture on Brand Identities in Johannesburg from 2012 to 2015 - Modiko, Keabetswe (The IIE, 2015)
It can be deliberated that music has occasionally been an intertwined part of human culture, the advancement of technology in modern society has created its increased accessibility and portability, which has led to unprecedented production and listening of this medium that enables individuals to enacts and perform various identities during everyday life. Research also shows that young people are consuming music more than any other age group. As a result music can in some respect be considered to be important cultural influencer in the lives of young individuals. Research that has been conducted thus far has been conducted in gaining understanding the various forms and functions of this influence has focused in the disciples that a linked to musicology and sociology. European and American psychologists have gained an interest in understanding the role that music has in constructing identity in young individuals. As a contribution to this field of application outside of these contexts and located within a qualitative framework, the purpose of this study is to explore the idea that the Hip Hop sub culture has an influence on the way brands have been positioning themselves from 2012 till 2015, specifically in South Africa. It debates whether or not Hip Hop music has had any impact on how brands in Johannesburg align themselves and create relevance to their target audiences. This research document will argue that Hip Hop culture is creating a new generation of consumers that are finding new ways of creating cultural expression that are redefining how young people are seeing themselves in post apartheid South Africa. Focusing the research on how brands like Ama Kip Kip (Sunday Times best SA brand 2013 and 2012 Old Mutual Teen Choice Award) and Nike S.A. have used Hip Hop to their advantage to grow their urban footprint in Johannesburg’s consumer landscape. The study will also look at how Hip Hop has been contextualized in South Africa to move away from its US cultural imperialist constrains (Adam Haupt, 2012).
Keywords: Branding; Hip Hop; Consumer Behaviour